Development of lower limb training interventions that promote an external focus of attention in people with stroke: a modified Delphi survey. (18th November 2022) - Johnson, Louise; Burridge, Jane; Demain, Sara
ABSTRACT: Objective: To produce guidance and validated examples of tasks that promote an external focus of attention, for use in lower limb rehabilitation in an inpatient stroke care setting. Design: Electronic survey, using e-Delphi methodology. Participants: A multi-professional expert panel of 14 clinicians and researchers, with expertise in stroke rehabilitation and/or motor learning. Method: Each survey round consisted of two parts: 1) classification of specific exercise examples, shown using video and 2) the categorization of specific tratement adjuncts. The panel was asked to comment on: likely focus of attention of the performer; instructions that would promote an external focus of attention; and how the task set-up could be modified to promote an external focus of attention. Rounds 2 and 3 included a summary of results from the previous round, and revised/new examples. The panel were also asked to state their level of agreement with a series of statements that arose from the free text. Three rounds of survey were completed and the a priori threshold for agreement was set at 80%. Results: Eighteen iterations of exercises were presented, and 12 were accepted as promoting an external focus of attention. In addition, six additional statements were generated based on open responses, leading to further specific guidance on facilitating an external focus of attention in clinical practice. Conclusions: Commonly used rehabilitation exercises can be adapted to promote an external focus of attention, by altering the therapist's use of instructions and/or altering the task set up. Treatment principles and examples of tasks that promote an external focus have been produced.